The Use of Animation Video as Online Learning Media to Teach English for Young Learners - Tri Pujiani; Windy Harsiwi; Neilia Almustaflikhah (Acitya: Journal of Teaching and Education, 2022)
During the pandemic of COVID-19, all teaching and learning activities had to be transformed into distance-learning or it was called Learning from Home. This immediate shift required all parties including teachers, parents, and students to be able to cooperate well. However, the implementation of this new learning method did not just run smoothly. Many factors influenced the effectiveness of Learning from Home, one of them was students' motivation to learn. Students, especially young learners, would be motivated to learn if the media used and the teaching method are interesting. Thus, in this research, animation video was developed as the online learning media for young learners. This research aimed to find out the effectiveness of animation video for teaching English to young learners viewed from the teachers and parents’ perspective. This was qualitative research with a descriptive approach. The data was obtained through observation, questionnaire distribution, and interviews. Then, the data was analyzed by data organization, data reduction, data description, data interpretation, and data validation. The result of this research revealed that the role of animation video as online learning media for young learners is effective to motivate the students to learn. It is expected that the result of this research may add scientific knowledge especially in the field of teaching English for young learners.